2018
DOI: 10.5603/ah.2018.0007
|View full text |Cite
|
Sign up to set email alerts
|

Zalecenia Sekcji Pediatrycznej Polskiego Towarzystwa Nadciśnienia Tętniczego dotyczące postępowania diagnostycznego i terapeutycznego w nadciśnieniu tętniczym u dzieci i młodzieży

Abstract: Presented recommendations are an extended and actualized version of paediatric recommendations of Polish Society of Hypertension published in 2015. Since then, new studies have appeared on this subject, introducing a new classification of hypertension, newly described principles of management in risk groups and methods of assessing hypertensive target organ damage. The presented updated recommendations included changes introduced in the 2016 European Society of Hypertension recommendations and Recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 109 publications
(133 reference statements)
2
24
0
1
Order By: Relevance
“…In our study we found no significant relation between blood pressure measured both in office and in ABPM and vitamin D status. As blood pressure in paediatric population is dependent on anthropometric variables (especially height) [1,2,20] it is recommended to index measurements to normative values. When expressed as Z-score the relation was stronger but still did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study we found no significant relation between blood pressure measured both in office and in ABPM and vitamin D status. As blood pressure in paediatric population is dependent on anthropometric variables (especially height) [1,2,20] it is recommended to index measurements to normative values. When expressed as Z-score the relation was stronger but still did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…In all children hypertension was confirmed using Polish Society of Arterial Hypertension and Polish Society of Paediatric Nephrology guidelines [1,2]. Secondary forms of hypertension were excluded by medical history and physical examination and by means of additional tests: renal function tests (creatinine, urea), serum ions (sodium, potassium, and calcium), capillary blood gases, urinalysis, and abdominal ultrasonography with evaluation of kidneys, urinary tract, adrenal glands, and blood flow in renal arteries.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following clinical data were collected from all CKD patients: age [years]; gender, aetiology of CKD according to ESPN/ERA-EDTA (European Society for Paediatric Nephrology/European Renal Association-European Dialysis and Transplantation Association) Registry (www.espn-reg.org/index.jsp); CKD stage according to KDIGO classification [11] based on estimated glomerular filtration rate (eGFR) derived by the modified Schwartz formula [12]; body mass [kg]; height [m] and body mass index (BMI) [kg/m 2 ] (Z-scores were calculated from national normative data [13]); hypertension diagnosed according to Polish Society of Hypertension guidelines [14]; and medications that might affect cardiovascular system. Overweight and obesity were defined according to World Health Organization definitions as BMI Z-score values > 1 and > 2, respectively.…”
Section: Methodsmentioning
confidence: 99%